Rancang Bangun Sistem Pendingin (Freezer)Penyimpanan Ikan Menggunakan Energi Surya (Photovoltaic) Pada Kapal Nelayan - Noerkhasyiin H, Andi Muhammad; Jaya, Farhan; Firman, Firman; Rahmah, Nur (Politeknik Negeri Ujung Pandang, 2025)
The utilization of renewable energy, which is currently a major focus due to the abundance of its raw materials and is highlighted by various countries, is the use of solar energy. Solar energy is a source of energy generated from abundant solar radiation that will never run out. Because solar energy can be accessed in almost all locations, it can be utilized, stored, and converted into electrical energy using existing technology. One technology that utilizes solar energy for conversion into electrical energy is solar panels. This research aims to design and develop a fish storage system that uses solar energy as the main power source. The research begins with the design and assembly of each component of the solar power system (PLTS) and the cooling system. Data collection is carried out by testing the assembled cooling system. Subsequently, the obtained data is analyzed to determine the Coefficient of Performance (COP). Based on this research, the maximum Coefficient of Performance (COP) of the tested cooling system is 0.173, with an observed COP range between 0.83 and 0.173. Testing was conducted under various operational conditions to evaluate the system's performance and find the optimal conditions.